Exploring the morphological variation of the hybrids between Crocodylus acutus and Crocodylus moreletii in the Mexican Caribbean through a 2D geometrics morphometric approach - Seculi Pereyra, Enzo Emanuel (2023)
Hybridization between species has been a controversial topic and it has attracted the attention of different areas in evolutionary biology. In México, this process is present in two crocodile species, Crocodylus acutus and Crocodylus moreletii. They occur sympatrically in the wild in the Peninsula of Yucatán, due to the accidental introduction of C. moreletii in the Oaxaca coast. The genetic and morphological diversity of the C. acutus population in the Mexican Caribbean are in trouble due the economic exploitation of the species through time, illegal trafficking, drowning in fishing nets, and genetic introgression of C. moreletii. Although some research exists about their genetics, there was no research done on hybrid morphology until now. In this sense, the goal of this study was to describe the morphological differences of the hybrids in relation to their parent species using geometrics morphometrics technique and determinate which factors (size, species and location) influence the shape of skull with randomized lineal models. The main morphological differences between species and hybrids were found in the viscerocranium region, being the left side of the hybrid skulls more similar to C. acutus and the right side more similar to C. moreletii. However, considering the skull as a whole, the hybrids were more similar to C. moreletii. This adds to previous results and provides evidence that C. acutus is losing both genetic and morphological diversity in Mexico. This result highlight the relevance of the insular population of C. acutus, which represents a genetic and morphological reservoir for the species.